Downregulation of miR-126-3p expression contributes to increased inflammatory response in placental trophoblasts in preeclampsia. (April 2021) - Chu, Xiaodan; Gu, Yang; Sheng, Wenji; Sun, Jingxia; Morgan, John A.; Lewis, David F.; Cooper, Danielle B.; McCathran, Charles E.; Wang, Yuping
Highlights: miR-126-3p expression significantly reduced in placental trophoblasts in preeclampsia. miR-126-3p is expressed in placental trophoblasts throughout pregnancy expression. Reduced miR-126-3p expression is reversely associated with increased IL-6 and TNFα production in trophoblasts from preeclamptic placentas. Transient overexpression of miR-126-3p significantly reduced IL-6 and TNFα. production in trophoblasts from both normal and preeclamptic placentas. Transient overexpression of miR-126-3p prevents hypoxia-induced increases in HIF1α expression and 8-Isoprostane production in placental trophoblasts. Abstract: MiR-126-3p is a prototype of an endothelial miRNA and has protective effects on endothelial cells. However, little is known about the effects of miR-126-3p on placental trophoblasts. In the present study, we tested the hypothesis that aberrant miR-126-3p expression is present in preeclamptic placenta which contributes to increased inflammatory response in trophoblasts. Placentas were obtained immediately after delivery from normotensive and preeclamptic pregnancies. Villous tissue was either fixed with formalin or used for trophoblast isolation. Trophoblast miR-126-3p expression was assessed by in situ hybridization of formalin-fixed tissue sections and by RT-PCR in cultured syncytiotrophoblasts. Culture medium was collected for measurement of IL-6, TNFα, and 8-Isoprostane production by ELISA and total cellular protein was collected for evaluation of HIF1α expression by Western blot. Effects of overexpression of miR-126-3p in trophoblasts on cytokine production were tested by transfection of pre-mir-126, a precursor of miR-126, into primary isolated trophoblasts. We found that downregulation of miR-126-3p expression was associated with increased IL-6 and TNFα production in trophoblasts from preeclamptic placentas vs. normal placentas. Moreover, transient overexpression of miR-126-3p significantly reduced IL-6 and TNFα production in trophoblasts from both normal and preeclamptic placentas. We further found that increase in miR-126-3p expression not only suppressed hypoxia-induced increases in IL-6 and TNFα production, but also attenuated hypoxia-induced increases in HIF1α expression and 8-Isoprostane production in trophoblasts cultured under hypoxic condition. These results provide plausible evidence that downregulation of miR-126-3p expression reduces anti-inflammatory and anti-oxidative stress activities in placental trophoblasts in preeclampsia.